Algebra Examples
y=x , (0,0) , (3,3)
Step 1
Write y=x as a function.
f(x)=x
Step 2
Step 2.1
The average rate of change of a function can be found by calculating the change in y values of the two points divided by the change in x values of the two points.
f(3)-f(0)(3)-(0)
Step 2.2
Substitute the equation y=x for f(3) and f(0), replacing x in the function with the corresponding x value.
(3)-(0)(3)-(0)
(3)-(0)(3)-(0)
Step 3
Step 3.1
Cancel the common factor.
(3)-(0)(3)-(0)
Step 3.2
Rewrite the expression.
1
1